Perkembangan Regulasi Diri Anak Usia Dini: Peranan Kemampuan Berbahasa dan Regulasi Diri pada Pembelajaran - Naili Sa'ida (PG-PAUD Trunojoyo, 2018)
This study aims to describe the development of self-regulation of children aged 4-5 years at Kindergarten Dhamawanita Persatuan Pucang Jajar. This study is a qualitative case study in children aged 4-5 years. Data analysis techniques use the model proposed by Miles and Huberman which consists of 3 stages: data reduction, data display, and verification. The research were use multi technique to collect the data use the observation, interviews, and documentation. The results showed that the development of self-regulation developed simultaneously with language skills. Language can really play an important role in determining how children regulate their thoughts, emotions, and behavior. Language facilitates the internalization of children's social structures and rules through their interaction in the social world around them. When children interact with others, their understanding of other people's perspectives and expectations is expanded. This perspective shows that language helps children understand their experiences, as well as the experiences of others, and so it is through language that children connect this information with their own behavior.